FORMATION OF CREATIVE COMPETENCES IN MODERN EDUCATION - Nuriddinov Khojiakbar (Academia Science Repository, 2023)
In the modern conditions of the development of society, the demands for creative pedagogues who are able to effectively use information resources in the educational process, are mobile, socially active, flexible to changes, and have non standard thinking are increasing more and more. Today, they are thinking about the need to implement creative pedagogy within the framework of education policy. " of rela tions between teachers and students to form creative individuals among pedagogues; humanistic ideas and humanitarian strategies in education, such as the student's active and interested participation in the educational process, are the basis [